SHOLAT TAHAJJUD SEBAGAI MANAJEMEN STRES PADA KARYAWAN DI UNIVERSITAS SAHID SURAKARTA - Faqih Purnomosidi (Psikoislamedia : Jurnal Psikologi, 2018)
Everyone will face problems in his life. Problems that are less able to be overcome properly often cause of stress. Stress is the body's response that is not specific to any demands or burdens on it so that not a few individuals who take the path are not good to overcome them. Conversely, not everyone who is experiencing stress overcomes it in a way that is not good. someone who is healthy in his faith and soul, physically and spiritually they are always excellent and healthy. Their closeness and submission to God makes them able to control stress well. One of the positive media that can be taken by a person in dealing with stress is the midnight prayer (Tahajjud Prayer). Tahajjud prayer provides many benefits, one of which can relieve stress for someone who is experiencing it. This study aim is to provide an overview of the Tahajjud prayer as stress management. Data collection methods in this study use interviews and observations. The informants in this study were two executive employees of the Prayers at the Sahid University of Surakarta. The results of the study show that the tahajjud prayers done by the informants are able to provide happiness in their lives. The sources of happiness are in the form of soul, peace of mind, comfort in life. So that the stress they experience can be overcome properly.